INFLUENCE OF DIFFERENT TYPES OF MILK AND STABILIZERS ON SENSORY EVALUATION AND WHEY SEPARATION OF YOGHURT (Biological Sciences - PJSIR, 2004)
The influence of seven different stabilizers i.e. pectin, guargum, carboxymethylcellulose (CMC), carrageenan, sodium alginate, corn starch and gelatin was studied at 0.4% levels in buffalo milk with 16.6% total solids, cow milk with13.5% total solids and mixture (1:1) of both having 15.0% on syneresis, body/texture, flavor, acidity and color in yoghurt. Results showed that corn starch gave best results in controlling synerises in yoghurt followed by gelatin, pectin, sodium alginate, carageenan, guargum and CMC in buffalo milk as compare to mixture and cow milk. Treatment (T19) having 0.4% corn starch and 16.6% total solids got maximum scores in flavor, body/texture, acidity and appearance than all other six stabilizers. This sample had firm coagulum, less separating whey, good aroma, pleasant taste and rheologically supe- rior to all other samples. Statistical analysis showed that the treatments, storage intervals and total solids had a significant effect (P